Matching land surface phenology with the phenology of net ecosystem exchange (NEE) in the Kruger National Park, South Africa - Ngubane, Dalingcebo (My University, 2021)
Vegetation phenology is controlled by complex interactions between bottom up factors such as rainfall and top down factors such as fire and herbivory. Climate change has been shown to already be impacting the lowveld savanna landscape and is already causing long-term changes in vegetation. Phenology plays an important role in the carbon cycle; and therefore, understanding how long-term changes in phenology translate to changes in the carbon cycle is important. Our understanding of the long-term complex relationship between phenology and the carbon cycle is limited by a lack of continuous monitoring of phenology and carbon fluxes over large spatial extents. Therefore, the aim of my study was to utilize remote sensing data to analyse the long-term (18 years) phenology patterns at a landscape level in the savanna region and the relationship between vegetation phenology and the carbon cycle. I found that there was an advance in the end of season in the southern bioregion of the Kruger National Park albeit not due to changes in rainfall as expected. Moreover, I found concurrent changes in phenology) at a localized level indicating an interactive effect of top-down and bottom-up factors. In addition, I showed that there is a strong relationship between FAPAR (Fraction of Absorbed Photosynthetically Active Radiation) and Net Ecosystem Exchange (NEE). Moreover, there is a strong relationship between the start of season predicted using remote sensing and the start of carbon uptake derived from in-situ eddy covariance NEE. My results suggest that the long-term changes in phenology, especially the localized changes, may be driving long term changes in the carbon flux.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2021
Keywords: Plant phenology; Climatic changes-South Africa